Nosocomial Fungemia Due to Exophiala jeanselmei var. jeanselmei and a Rhinocladiella Species: Newly Described Causes of Bloodstream Infection - Nucci, Marcio (American Society for Microbiology, 2001)
Fungi have become increasingly important causes of nosocomial bloodstream infections. The major cause of nosocomial fungemia has been Candida spp, but increasingly molds and other yeasts have caused disease. Exophiala jeanselmei and members of the genus Rhinocladiella are dematiaceous moulds, which have been infrequently associated with systemic infection and have not been described as causes of fungemia. In this paper, the occurrence of 23 cases of fungemia due to these organisms over a 10-month period is reported and the clinical characteristics of patients and outcomes are described. The majority of patients were immunosuppressed; 21 of 23 (91%) had received blood products and 78% had a central venous catheter. All patients had at least one manifestation of fever, but only one patient had signs or symptoms suggesting deep-seated infection. Antifungal therapy was given to 19 of the 23 patients; of those who did not receive therapy, 3 died prior to the culture result and 1 had been discharged without therapy. Antifungal susceptibility of the organisms showed activity of amphotericin B, itraconazole, and the new triazole antifungals voriconazole and posaconazole. E. jeanselmei and Rhinocladiella species are potential causes of nosocomial fungemia and may be associated with systemic infection.